Request for specifying the location of Davit arm at roof floor of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding request for specifying the location of Davit arm at roof floor of BRAC University new campus project.